Psoriasis, arthritis, autoimmune hepatitis and dystrophic calcinosis in a 15-year-old girl. - Milano, A.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
A 15-year-old girl was first observed with a 4-year history of cutaneous lesions, joint pain and chronic autoimmune hepatitis. The clinical and laboratory investigations led to diagnose psoriasis, that during the follow up presented clinical features of plaque and guttate psoriasis, and symmetrical, polyarticular psoriatic arthritis. The diagnosis of autoimmune hepatitis was confirmed. There was also dystrophic calcinosis around the elbow and knee joints. The patient was treated with topical and low dosage systemic immune suppressive therapy, whereas no treatment was given for calcinosis.